Antibacterial activity of Acalypha indica extract on Porphyromonas gingivalis: An in vitro study - Prarthana Manoharan; Lalithambigai Gunasekaran; Girish R Shavi; Shankar Shanmuagam; John J Smith (Wolters Kluwer Medknow Publications, 2023)
Introduction: Acalypha indica plant is traditionally used to treat dysentery, diarrhea, malnutrition, and malaria. This plant extract reported a wide antibacterial spectrum against Staphylococcus aureus, Staphylococcus epidermidis, Bacillus cereus, Streptococcus faecalis, and Pseudomonas aeruginosa. Objective: This study aimed to assess the antimicrobial efficacy of A. indica plant extract at the concentrations of 10-200 mg/ml against Porphyromonas gingivalis. A. indica plant metabolites were extracted by the maceration technique using methanol. Materials and Methods: The literature revealed the analysis of different phytochemicals such as alkaloids, flavonoids, tannins, saponins, and phenols. The antibacterial activity was analyzed using minimum inhibitory concentration (MIC) and minimum bactericidal concentration. Results: The n-hexane extract of A. indica has the best antibacterial potency at 200 mg/ml against P. gingivalis with an initial zone of inhibition at 100 mg/ml 12 mm, which is compared to the gold-standard chlorhexidine and MIC value of 150 mg/ml. Conclusion: Among major periodontal pathogens, P. gingivalis appears to be one of the prime etiological agents in the pathogenesis and progression of the inflammatory events of periodontal disease. This infinitesimal herb A. indica found throughout India is readily available and can be utilized as an effective antimicrobial agent against P. gingivalis and periodontal diseases.